2021
DOI: 10.1103/physreva.104.043327
|View full text |Cite
|
Sign up to set email alerts
|

Lossy quantum defect theory of ultracold molecular collisions

Abstract: We consider losses in collisions of ultracold molecules described by a simple statistical short-range model that explicitly accounts for the limited lifetime of classically chaotic collision complexes. This confirms that thermally sampling many isolated resonances leads to a loss cross section equal to the elastic cross section derived by Mayle et al. [Phys. Rev. A 85, 062712 (2012)] and this makes precise the conditions under which this is the case. Surprisingly, we find that the loss is nonuniversal. We also… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…Thus in a gas of temperature T ≈ 0.5 µK, the number of resonances directly relevant would be of order unity at best, and far below this in general. Additional resonances could be relevant if they are very broad, but this remains uncertain at present [40].…”
Section: Methods and Modelmentioning
confidence: 98%
“…Thus in a gas of temperature T ≈ 0.5 µK, the number of resonances directly relevant would be of order unity at best, and far below this in general. Additional resonances could be relevant if they are very broad, but this remains uncertain at present [40].…”
Section: Methods and Modelmentioning
confidence: 98%
“…The RRKM model may be applicable. 130 For atom–molecule collisions, the density of states is much lower and the mean spacing between neighboring states is much larger than the temperature of the molecular gases. In this case, thermal averaging may be inappropriate.…”
Section: Ultracold Collisionsmentioning
confidence: 99%
“…In the absence of other loss processes, this implies a mean lifetime τ = 2π ρ/T inc , but only if the thermal energy spread is large compared to Γinc as described above. Christianen et al [83] recently considered a lossy QDT model of such resonances. They concluded that if the complexes are lost rapidly once formed and Γs inc = d/2π, such that T s inc = 1 in equation ( 3), the loss rate is represented by y = 0.25, as opposed to the y = 1 implicit in the model of Croft et al [82].…”
Section: Resonance Widths and Lifetimes Of Collision Complexesmentioning
confidence: 99%
“…However, when many resonances overlap, they reach the regime of Ericson fluctuations [80] and the total loss cannot be represented in this way. This situation has been considered by Christianen et al [83]. Here we will consider only the case Γ inel < d, which is applicable to typical alkali atom + diatom collisions.…”
Section: Resonance Widths and Lifetimes Of Collision Complexesmentioning
confidence: 99%